French-Serbian relations, history and memories: The heritage of World War I - Sretenović Stanislav (Nasleđe, 2018)
Any even remotely observant and curious visitor in Belgrade will notice the amount and beauty of the French-Serbian memorial sites. Engraved in the turbulent and complex history of Europe, these places testify to the strong and deep ties once established between the two nations. Throughout history, the French and the Serbs have invested great efforts to overcome the physical distance, material disproportion and cultural diversity - a multitude of factors that could have stood as a boundary to their relationship. Nowadays, Serbs can be proud of the fact that they are one of the few nations in Eastern Europe with such a rich tangible and non-tangible heritage manifesting the French universal values - freedom, justice, democracy and human rights. In this article, the author deals with the evolution of relationship between France and Serbia in the 19th and 20th century, underlining the importance of their alliance in the World War I, analyzing their fortification between the two world wars, the relationship now being written in stone, and explaining the interpretation of the Franco-Serbian past at the beginning of the World War II.